2001
DOI: 10.1046/j.1440-1614.2001.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Risk Factors for Postnatal Depression in Urban and Rural Community Samples

Abstract: The results emphasize the importance of psychosocial risk factors for postnatal depression and suggest that most obstetric factors during pregnancy and birth do not significantly increase risk for this depression. Early identification of potential risk for postnatal depression should include assessment of sociodemography, personality, psychiatric history and recent life events, as well as past and present obstetric factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
108
1
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(147 citation statements)
references
References 27 publications
26
108
1
12
Order By: Relevance
“…In the same study, it was found out that PPD was significantly more in women with nuclear families which were consistent with the findings of our study [10]. Our results also showed no association of PPD with obstetric risk factors like present or previous pregnancy and delivery complications which were similar to findings of the previous studies [18,19] and were conflicting with the findings of study done in Victoria [20]. This unusual finding may be attributed to improved and better health One finding that husband's alcohol intake is associated with PPD is unique to Indian culture in sharp contrast to western countries where both men and women consider alcohol intake as normal.…”
Section: Discussionsupporting
confidence: 93%
“…In the same study, it was found out that PPD was significantly more in women with nuclear families which were consistent with the findings of our study [10]. Our results also showed no association of PPD with obstetric risk factors like present or previous pregnancy and delivery complications which were similar to findings of the previous studies [18,19] and were conflicting with the findings of study done in Victoria [20]. This unusual finding may be attributed to improved and better health One finding that husband's alcohol intake is associated with PPD is unique to Indian culture in sharp contrast to western countries where both men and women consider alcohol intake as normal.…”
Section: Discussionsupporting
confidence: 93%
“…Instead, unexpectedly, unwanted last pregnancy was significantly higher in non PPD group. These findings were congruent with findings of researchers elsewhere regarding the number of pregnancies 11 ; number of children 13 ; number of abortions 17 ; number of stillbirths 13,18 ; gender of the last baby 13,19 ; mode of the last labor 20 ; and history of marital and other psychosocial problems during last pregnancy 21 . However, In contrast to our results, a longitudinal study among Chinese mothers in Hong Kong found that 2 or more previous induced abortions are significant predictors of PPD 22 .…”
Section: Obstetrical Risk Factorssupporting
confidence: 90%
“…Two studies found no significant differences in the risk of depression at 6-8 weeks postpartum. 20,21 In the third study, Australian women from nonmetropolitan areas (n = 213) had significantly lower odds (OR 0.54, 95% CI 0.33-0.90) of depression at 8-9 months postpartum than did women living in metropolitan areas (n = 535). 22 These results are not surprising, because outcomes can change depending on the definition of the rural exposure group.…”
Section: Discussionmentioning
confidence: 94%